PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 009 SUNGAI BAKAU KECAMATAN SINABOI KABUPATEN ROKAN HILIR - Maysarah '; Syahrilfuddin '; Zariul Antosa Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Problem background of this research that student do not understand about IPA lesson. The average score result of IPA test is 60,5. And only 7 of 20 student or 35% in class can reach standard of KKM, while score of KKM is 75. This is the problem: “Do the Inkuiri Learning Model can improve IPA studying result, Student of class III SD Negeri 009 Sungai Bakau Kecamatan Sinaboi Kabupaten Rokan Hilir?”. This research form is Observation of Class Action/ Penelitian Tindakan Kelas (PTK). This is the hypothesis of this research: “If the Direct Learning Model is applied therefore gets to increase IPA studying results, Student of class III SD Negeri 009 Sungi Bakau Kecamatan Sinaboi Kabupaten Rokan Hilir?”. This research is done as much 2 cycles with 6 appointments, there are 4 presentations and 2 times of test. After that, data is collected and analyzed. Test I (UH I) shows the increasing average score, from basic score 60,5 to be 74, its increase 13,5 points. And at the Test II (UH II) increase about 8 points. So that, the average score is to be 82 at the Test II. So, total increasing from basic score to Test II (UH II) is 21,5 points. The Classically Completing activity also increase about 35%, basic score percentage 30% at the Test I to be 65%. And at the Test II, percentage score is 85%, its increase 20%. Besides that, activity of teacher and student are increasing in every meeting. Percentage of teacher activity at the first meeting is 62,5%, and at the second is 70,83% (increase 8,33%). Fourth meeting, teacher activity is 79,17% (8,34%), and 91,67% (12,5%) at the fifth meeting. Student activity at the first meeting is 54,17%, and 62,5% (8,33%) at the second meeting. There is increasing to be 70,83% (8,33%) at the fourth meeting, and 91,67% (20,84%) at the fifth meeting. So, the conclusion is the Implementation of Inkuiri Learning Model can increase IPA studying result, Student of class IV SD Negeri 009 Sungai Bakau Kecamatan Sinaboi. Keywords: Inkuiri Learning, IPA studying result